1994
DOI: 10.1111/j.1574-6976.1994.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial behaviour in salt-stressed ecosystems

Abstract: Salt stress is primarily osmotic stress, and halophilic/halotolerant microorganisms have evolved two basic mechanisms of osmoadaplation: the KCI‐type and the compatible‐solute type, the latter representing a very flexible mode of adaptation making use of distinct stabilizing properties of compatible solutes. A comprehensive survey, using HPLC and NMR methods, has revealed the full diversity of euhacterial compatible solutes found in nature. With the exception of proline (a proteinogenic amino acid) they are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
212
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(219 citation statements)
references
References 80 publications
4
212
0
3
Order By: Relevance
“…In wetlands, these factors include light, redox potential, salinity, carbon substrate availability, inorganic N and P concentrations, Fe and Mo, availability and grazers (Capone & Kiene, 1988;Howarth et al, 1999). In saline environments, bacteria have to cope with ionic stress, which is balanced by intracellular osmoprotective compounds, many of which are sugars (e.g., disaccharide trehalose, Welsh & Herbert, 1999) or contain N (amino acids and their derivatives such as glycine betaine, Csonka, 1989;Galinski & Trüper, 1994). N fixation thus provides an important source of N in these, often N-limited, environments (Casselman et al, 1981;Whiting & Morris, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In wetlands, these factors include light, redox potential, salinity, carbon substrate availability, inorganic N and P concentrations, Fe and Mo, availability and grazers (Capone & Kiene, 1988;Howarth et al, 1999). In saline environments, bacteria have to cope with ionic stress, which is balanced by intracellular osmoprotective compounds, many of which are sugars (e.g., disaccharide trehalose, Welsh & Herbert, 1999) or contain N (amino acids and their derivatives such as glycine betaine, Csonka, 1989;Galinski & Trüper, 1994). N fixation thus provides an important source of N in these, often N-limited, environments (Casselman et al, 1981;Whiting & Morris, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…De telles variations osmotiques étant délétères pour les bactéries, celles-ci possèdent des systèmes de transport et/ou de synthèse d'osmoprotectants ou solutés compatibles qui assurent le maintien de l'homéostasie par leur accumulation dans le cytoplasme ou leur rejet selon le type de stress osmotique [4,5,17]. Les solutés compatibles sont des composés organiques qui peuvent être accumulés à forte concentration dans le cytoplasme sans interférer avec les processus cellulaires, la molécule majeure étant la glycine bétaïne (N,N,N-trimethylglycine), qui appartient à la famille des composés ammonium quaternaires [8].…”
Section: Introductionunclassified
“…It was suggested that betaine might be synthesized from glycine by a series of methylation reactions in archaebacterium Methanohalophilus portucalensis (12) and anaerobic phototrophic sulfur bacterium Ectothiorhodospira halochloris (13). Betaine synthesis from simple carbon sources has also been suggested in aerobic heterotrophic eubacterium Actinopolyspora halophila (13) and halotolerant cyanobacterium of Aphanothece halophytica (14).…”
mentioning
confidence: 99%